Effects of different formulation PEDOT:PSS hole transport layers on photovoltaic performance of organic solar cells - Ongul, Fatih; Yuksel, Sureyya Aydin; Kazici, Mehmet; Bozar, Sinem; Gunbatti, Anil; Gunes, Serap (WILEY, 2017)
In this study, the effects of the various types of PEDOT:PSS with different conductivities on the photovoltaic parameters of organic solar cells were investigated. The performances of five various commercially available PEDOT:PSS with formulations such as FET, PT2, PH1000, PH500 and PH were compared. It was observed that the device employing PH1000 as an interlayer between ITO and the active layer exhibited the highest photovoltaic performance as compared to other devices with FET, PT2, PH500 and PH. Copyright (c) 2015 John Wiley & Sons, Ltd.
Keywords: PEDOT:PSS; conducting polymers; hole transport layer; organic solar cells; POLY(3,4-ETHYLENEDIOXYTHIOPHENE) POLY(STYRENESULFONATE); PEDOT/PSS FILMS; THIN-FILMS; PSS LAYER; POLYMER; CONDUCTIVITY; MORPHOLOGY; EFFICIENCY; DEGRADATION; ADDITIVES; Polymer Science